Agreement between Thyroid Uptake of 99mTc Pertechnetate and 131I in Hyperthyroid Patients - Hossain, Sadia; Hossain, Sanowar; Haque, Fatema S; Biswas, Shanker K; Begum, Rubina; Rahman, Farhana; Afreen, Rawnak; Hossain, Mohona; Akhter, Afroza; Sultana, Tania; et al. (Bangladesh Journal of Nuclear Medicine, 2018)
Objectives: With the advancement of science, the scope of 131 I thyroid uptake in diagnosis and treatment of thyroid diseases has become limited. Uptake test with 99m Technetium (99mTc) pertechnetate along with a thyroid scan, which are done almost routinely, could be a better option when required. This will not only exempt the patients from relatively higher radiation burden of 131I but will also cause significant reduction of procedural time. Moreover, the thyroid image we get along with the uptake may guide with additional information. This study was done to provide preliminary data regarding thyroid uptake test with 99mTc in our population & to assess the possibilities of introducing this safer and convenient radionuclide in our routine practice. Patients and methods: This cross sectional, comparative study was conducted from January to December of 2015 on 27 participants in Institute of Nuclear Medicine and Allied Sciences, Dhaka. Hyperthyroid patients coming for a radioactive iodine uptake test along with a thyroid scan were enrolled. Uptake of 99mTc pertechnetate at 20 minutes and 131I at 24 hours were measured. Results: Among 27 participants, 25 had raised, 2 had normal 131I uptake. Two normal values of 99m Tc uptake were found and rest showed high uptake. Two patients had high uptakes in both the method but 131 I uptake was extremely high (90% and 80%) in comparison to 99mTc uptake (10% and 7% respectively). Statistical analysis revealed a moderate agreement (k=0.5) along with a moderate positive correlation (r=0.6) between the two uptake methods. Conclusion: Good agreement and correlation were found between two modalities of thyroid uptake in case of hyperthyroid patients. So, 99mTc may be considered for uptake test in a regular basis in the limited fields where an uptake is still required as it may yield a reliable result in a simple, quicker and more convenient way. Bangladesh J. Nuclear Med. 19(2): 89-91, July 2016